Pengaturan Predatory Pricing Transportasi Online Dalam Perspektif Hukum Persaingan Usaha - Ni Putu Yuley Restiti; Ni Luh Mahendrawati; Ni Made Sukaryati Karma (Fakultas Hukum Universitas Warmadewa, 2021)
In the business world, competition between business people is common. Business actors that conduct fair business competition will have a positive impact on the course of competition between other business actors. However, in reality there are also business actors who conduct business competition in unhealthy ways that will adversely affect the balance in business competition. The problems of this study are: 1) What is the predatory pricing arrangement in business competition in Indonesia and 2) What is the relevance of promotion as an online transportation marketing tool for legal arrangements for predatory pricing. The research method used is a normative legal research method so that the problem approach used is the legal, conceptual, and case approaches and uses primary and secondary legal materials. So that legal material collection techniques used are documentation techniques by processing and analyzing legal materials that have been collected using legal arguments. As for the results of this research are the regulation regarding the prohibition on practicing predatory pricing is contained in Article 20 of Constitution No. 5 of 1999 concerning Prohibition of Monopolistic Practices and the relevance of promotion as a means of online transportation marketing to the legal arrangements of predatory pricing in Constitution No. 5 of 1999 which has not regulated excessive promotion at a very low price which can lead to elements of predatory pricing practices.